The Architecture of Happiness. (October 2022) - Lomas, Tim; Bartels, Meike; Van De Weijer, Margot; Pluess, Michael; Hanson, Jeffrey; VanderWeele, Tyler J.
Happiness is an increasingly prominent topic of interest across academia. However, relatively little attention has been paid to how it is created, especially not in a multidimensional sense. By 'created' we do not mean its influencing factors, for which there is extensive research, but how it actually forms in the person. The work that has been done in this arena tends to focus on physiological dynamics, which are certainly part of the puzzle. But they are not the whole picture, with psychological, phenomenological, and socio cultural processes also playing their part. As a result, this paper offers a multidimensional overview of scholarship on the 'architecture' of happiness, providing a stimulus for further work into this important topic.